Mutu Modal Manusia dan Pertumbuhan Ekonomi - H Hardjanto (Jurnal Manajemen Hutan Tropika, 2002)
This paper present a correlation between human capital and economic grawrh. There are two important points concerning this correlation, First, human capital should be put on the same priorih as other factor in economic growth. Second, human capital has a significant impact on the economic growth.